Comparative analysis of serum homocysteine, folic acid and vitamin B12 levels in patients with noise-induced hearing loss - Gok, U; Halifeoglu, I; Canatan, H; Yildiz, M; Gursu, MF; Gur, B (Elsevier Sci Ltd, 2004)
Objective: The aim of the present study was to determine the levels of homocysteine, folic acid, and Vitamin B-12 in subjects with noise-induced hearing loss. Furthermore, possible links between these parameters and noise-induced hearing loss were aimed to be evaluated. Methods: In the present study, blood samples were obtained from all subjects after overnight fasting for biochemical analysis. We examined the levels of homocysteine, Vitamin B-12 and folic acid levels in subjects with noise-induced hearing loss. Twenty-eight male patients with noise-induced hearing loss (mean age 37 +/- 5 year) were included in the study group whereas the control group was composed of 32 healthy male volunteers (mean age 36 +/- 4 year). Results: It was found that homocysteine levels of subjects with noise-induced hearing loss as significantly high compared to healthy controls (P < 0.05). On the other hand, Vitamin B-12 and folic acid levels of patients with noise-induced hearing loss were determined to be significantly low compared to the controls (P < 0.05 and < 0.01, respectively). Conclusion: Our findings indicate that there might be a link between increased homocysteine levels and noise-induced hearing loss. Since increased homocysteine levels cause elevated levels of free radicals in addition to its atherogenic and thrombogenic effects. Further experimental studies are needed to decipher how this relationship is linked. (C) 2003 Elsevier Ireland Ltd. All fights reserved.
Keywords: noise-induced hearing loss; homocysteine; vitamin B-12; folic acid